Abbreviated MRI-Based Surveillance Strategies for Early Hepatocellular Carcinoma Detection - Hyo Jung Park; Dong Wook Kim; Won-Mook Choi; So Yeon Kim (Journal of the Korean Society of Radiology)
Although US has been widely used for hepatocellular carcinoma (HCC) surveillance, it exhibits limited sensitivity for detecting early-stage HCC. Abbreviated MRI (AMRI) has attracted attention as a superior alternative, offering higher sensitivity for early-stage HCC detection than US and reduced imaging time and cost compared to comprehensive contrast-enhanced MRI. AMRI focuses on essential sequences tailored for HCC detection, with three main strategies: gadoxetate disodium-enhanced hepatobiliary phase AMRI, dynamic contrast- enhanced AMRI, and non-contrast AMRI. In this review, we aim to highlight the technical considerations, performance, and strengths and limitations of each AMRI strategy as well as reporting strategies and recall practices. In addition, to maximize HCC surveillance efficacy using AMRI, a risk-adapted strategy tailored to different patient groups would be necessary, which we will also explore in this review.